Skeletal muscle glycogen concentration and metabolic responses following a high glycaemic carbohydrate breakfast - Chryssanthopoulos, C.; Williams, C.; Nowitz, A.; Bogdanis, G. (Journal of Sports Sciences, 2005)
The purpose of this study was to examine the influence of a carbohydrate-rich meal on post-prandial metabolic responses and skeletal muscle glycogen concentration. After an overnight fast, eight male recreational/club endurance runners ingested a carbohydrate (CHO) meal (2.5 g CHO?·?kg-1 body mass) and biopsies were obtained from the vastus lateralis muscle before and 3 h after the meal. Ingestion of the meal resulted in a 10.6?±?2.5% (P?<?0.05) increase in muscle glycogen concentration (pre-meal vs post-meal: 314.0?±?33.9 vs 347.3?±?31.3 mmol?·?kg-1 dry weight). Three hours after ingestion, mean serum insulin concentrations had not returned to pre-feeding values (0 min vs 180 min: 45?±?4 vs 143?±?21 pmol?·?l-1). On a separate occasion, six similar individuals ingested the meal or fasted for a further 3 h during which time expired air samples were collected to estimate the amount of carbohydrate oxidized over the 3 h post-prandial period. It was estimated that about 20% of the carbohydrate consumed was converted into muscle glycogen, and about 12 % was oxidized. We conclude that a meal providing 2.5 g CHO?·?kg-1 body mass can increase muscle glycogen stores 3 h after ingestion. However, an estimated 67% of the carbohydrate ingested was unaccounted for and this may have been stored as liver glycogen and/or still be in the gastrointestinal tract.